СОВРЕМЕННЫЕ АСПЕКТЫ ВНЕДРЕНИЯ СИМУЛЯЦИОННОГО ОБУЧЕНИЯ У СТУДЕНТОВ ПЕДИАТРИЧЕСКОГО ФАКУЛЬТЕТА - Сапотницкий, Алексей Вячеславович; Мирончик, Наталья Васильевна; Сукало, Александр Васильевич; Прилуцкая, Вероника Анатольевна; Зайцева, Елена Семеновна (Медицина: теория и практика, 2020)